Techniques and strategies for regional anesthesia in acute burn care—a narrative review. Issue 1 (17th July 2021) - Sheckter, Clifford C; Stewart, Barclay T; Barnes, Christopher; Walters, Andrew; Bhalla, Paul I; Pham, Tam N
Abstract: Burn injuries and their treatments result in severe pain. Unlike traumatic injuries that are characterized by a discrete episode of pain followed by recovery, burn-injured patients endure pain for a prolonged period that lasts through wound closure (e.g. background pain, procedural pain, breakthrough pain, neuropathic pain and itch). Regional anesthesia, including peripheral nerve blocks and neuraxial/epidural anesthesia, offers significant benefits to a multimodal approach in pain treatment. A 'regional-first' approach to pain management can be incorporated into the workflow of burn centers through engaging regional anesthesiologists and pain medicine practitioners in the care of burn patients. A detailed understanding of peripheral nerve anatomy frames the burn clinician's perspective when considering a peripheral nerve block/catheter. The infra/supraclavicular nerve block provides excellent coverage for the upper extremity, while the trunk can be covered with a variety of blocks including erector spinae plane and quadratus lumborum plane blocks. The lower extremity is targeted with fascia iliaca plane and sciatic nerve blocks for both donor and recipient sites. Burn centers that adopt regional anesthesia should be aware of potential complications and contraindications to prevent adverse events, including management of local anesthetic toxicity and epidural infections. Management of anticoagulation around regional anesthesia placement is crucial to prevent hematoma and nerve damage. Ultimately, regional anesthesia can facilitate a better patient experience and allow for early therapy and mobility goals that are hallmarks of burn care and rehabilitation.